Academe-Industry-Government Collaboration Framework for Sustainable Research, Development and Extension (RDE) - Torrentira, Jr., Moises C. (JPAIR Institutional Research, 2015)
When sectors collaborate, they effectively contribute to the economic growth. Hence, a collaborative governance framework is developed for the academe, industry and government to sustain their research, development and extension. To generate dimensions of the collaboration, data from key informant interview and comprehensive desk review were processed through thematic content analysis. Typologies of RDE collaboration were identified including capability-building, management partnership, institutional partnership, and reinforcement. In terms of governance, RDE collaboration can be sustained through personal relation, established rapport, and transparency. Political leadership, micro-leadership, and leadership by character can also sustain RDE collaboration. In prioritizing research agenda, stakeholders must be involved and their thrusts and priorities should be considered. The academe’s resources and R & E enabling environment, faculty’s motivation can also sustain the collaboration. Conditions that inhibit collaborations were also identified but they can be addressed by the identified strategic actions. The study concluded with the formulation of collaborative governance framework between academe, industry, and government for sustainable research, development, and extension. The framework was developed based on the models of collaborative governance, collaborative leadership, prioritized R&E agenda, motivation to conduct RDE projects, and strategic actions to address the R & E collaboration issues.